Determining the overall sensitivities of swiss chard to cucurbitacin-containing phytonematicides under different conditions - Mashela, Tshepo Segwadi (My University, 2020)
The unavailability of environment-friendly nematicides for managing root-knot (Meloidogyne species) nematodes in crop husbandry have led to various alternative methods being sort which includes the development of cucurbitacin-containing phytonematicides. The cited phytonematicides consistently suppressed nematode numbers on different crops under greenhouse, microplot and field conditions, although there is lack of information on how the products would affect susceptible Swiss chard infected by root-knot nematodes. Swiss chard is one of most nutritious vegetables, grown throughout the year and is well adapted to different soil types. However, these products have the potential to induce phytotoxicity on various crops, if applied improperly. Phytotoxicity of phytonematicides on different crops, has been resolved by deriving Mean Concentration Stimulation Point (MCSP). The MCSP, developed using the Curve-fitting Allelochemical Response Data (CARD) computer-based model, is crop-specific, hence it should be developed for every crop. The objectives of this study were to investigate (1) whether population densities of Meloidogyne species, growth and accumulation of selected nutrient elements in Swiss chard would respond to increasing concentration of Nemarioc-AL and Nemafric-BL phytonematicides under greenhouse and microplot conditions and (2) whether the nemarioc-group and nemafric-group phytonematicides in liquid and granular formulations would affect population densities of Meloidogyne species and the productivity of Swiss chard with related accumulation of nutrient elements in leaf tissues under field conditions. Parallel experiments for Nemarioc-AL and Nemafric-BL phytonematicides were conducted concurrently under greenhouse and microplot conditions. Greenhouse experiment was prepared by arranging 25-cm-diameter plasticpods on greenhouse benches, whereas microplot experiment was prepared by digging holes and inserting 30-cm-diameter plastic pots in the field. The four-week-old Swiss chard seedlings were transplanted into the pots, filled with steam-pasteurised loam, sand and Hygromix-T at 3:1:1 (v/v) ratio. Treatments comprised 0, 2, 4, 8, 16, 32 and 64% phytonematicides arranged in randomised complete block design (RCBD), with six replications. Treatments were applied seven days after inoculation, with 3000 eggs and J2 of M. incognita race 4 under greenhouse conditions, whereas under microplot conditions were inoculated with 6000 eggs and J2 of M. javanica. Under field conditions, treatments comprised untreated control (0), 2 g Nemarioc-AG and 3% Nemarioc-AL phytonematicides (nemarioc-group) or 0, 2 g Nemafric-BG and 3% Nemafric-BL phytonematicides (nemafric-group), arranged in RCBD, each experiment with 8 replications. At 56 days after initiation of treatments, eggs in roots, J2 in roots and Pf exhibited negative quadratic relations under both greenhouse and microplot conditions. Under greenhouse conditions, dry shoot mass (R2 = 0.81), dry root mass (R2 = 0.87) and leaf number (R2 = 0.91) over Nemarioc-AL phytonematicide exhibited positive quadratic relations. In contrast, dry shoot mass (R2 = 0.78), dry root mass (R2 = 0.93) and leaf number (R2 = 0.70) over Nemafric-BL phytonematicide exhibited positive quadratic relations. Under microplot conditions, dry shoot mass (R2 = 0.95) and gall rating (R2 = 0.96) over Nemarioc-AL phytonematicide, exhibited positive quadratic relations. Dry shoot mass (R2 = 0.84) and gall rating (R2 = 0.97) versus Nemafric-BL phytonematicide exhibited positive quadratic relations. Selected nutrient elements under greenhouse conditions K (R2 = 0.96), Ca (R2 = 0.79), Mg (R2 = 0.64), Fe (R2 = 0.78) and Zn (R2 = 0.77) over Nemarioc-AL phytonematicide exhibited positive quadratic relations. In contrast, only Ca (R2 = 0.90), Mg (R2 = 0.68) and Zn (R2 = 0.84) over Nemafric-BL phytonematicide exhibited positive quadratic relations, whereas K (R2 = 0.72) and Fe (R2 = 0.63) over the product exhibited negative quadratic relations. Under microplot conditions, K (R2 = 0.82), Ca (R2 = 0.90) and Mg (R2 = 0.98) over Nemarioc-AL phytonematicide exhibited positive quadratic relations, whereas Fe (R2 = 0.91) and Zn (R2 = 0.79) over the product exhibited negative quadratic relations. In contrast, K (R2 = 0.60), Ca (R2 = 0.68) and Zn (R2 = 0.95) over Nemafric-BL phytonematicide exhibited positive quadratic relation, whereas Mg and Fe over the product did not have significant relationships. Under greenhouse conditions, MCSP values for Nemarioc-AL and Nemafric-BL phytonematicides on Swiss chard were 3.03 and 2.36%, whereas overall sensitivity (∑k) values of the crop to the product were 3 and 0 units, respectively. In contrast, MCSP values of Nemarioc-AL and Nemafric-BL phytonematicides on Swiss chard under microplot conditions was successfully established at 3.71 and 3.33%, whereas the ∑k values were 2 and 1 units, respectively. Under field conditions, at 64 days after initiating the treatments, the nemarioc-group phytonematicides had highly significant effects on eggs in roots and reproductive potential (RP), contributing 79 and 77% in total treatment variation (TTV) of the respective variables. In contrast, the nemafric-group phytonematicides had highly significant effects on eggs in roots and RP, contributing 67 and 76% in TTV of the respective variables. Under field conditions, all plant growth variables were not significantly affected by the treatments. The nemarioc-group phytonematicides had significant effects on K and Mg in leaf tissues of Swiss chard, contributing nemafric-group phytonematicides had significant effects on Mg, contributing 62% in TTV of the variable. In conclusion, the products could be used on Swiss chard for managing population densities of Meloidogyne species. However, due to the sensitivity of Swiss chard to the products, it would be necessary to use the derived MCSP values to determine the application intervals of the products on the test cultigen
Thesis (M.Sc. (Agriculture, Plant Protection)) -- University of Limpopo, 2020
Keywords: Meloidogyne species; husbandry; nutritious vegetables; cucurbitacin-containing; phytonematicides; Swiss chard; Nematocides